(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
SOMMARIO: 1. Sempre a proposito dell’art. 7 d.p.r. n. 285 del 1990 - 2. Un recente caso locale - 3. Una nuova frontiera del “classico”? Citare un testo che non esiste - 4. Qualche precisazione in materia di circolari - 5. Conclusione. The sleep of argumentation produces (legal) monsters ABSTRACT: This writing is intended to reply to certain allegations concerning the burial of aborted foetuses in the absence of the mother’s consent. A recent local news case is also reported. In addition, some theoretical and practical aspects of the legal instrument of the circular are clarified.